2020
DOI: 10.1038/s41598-020-64736-4
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological lesions and exposure to Plasmodium falciparum infections in the placenta increases the risk of preeclampsia among pregnant women

Abstract: Preeclampsia (PE) is a placental disorder with different phenotypic presentations. In malaria-endemic regions, high incidence of PE is reported, with debilitating foeto-maternal effects, particularly among primigravid women. However, the relationship between placental pathology and Plasmodium falciparum infection in the placenta with PE is underexplored. Placentas from 134 pregnant women were examined after delivery for pathological lesions and placental malaria (PM). They comprised of 69 women without PE (non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 46 publications
0
16
1
Order By: Relevance
“…The extent to which PM and PM/HIV coinfection may contribute to preeclampsia via MPO production or modification of other neutrophil functions remains to be determined. This may be an exciting avenue to pursue given increasing evidence that malaria predisposes women to this hypertensive disorder ( 91 , 92 ).…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which PM and PM/HIV coinfection may contribute to preeclampsia via MPO production or modification of other neutrophil functions remains to be determined. This may be an exciting avenue to pursue given increasing evidence that malaria predisposes women to this hypertensive disorder ( 91 , 92 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of pro-inflammatory cytokines, oxidative stress [ 27 ], and apoptosis lead to pathological changes in the placenta and poor pregnancy outcomes [ 28 ]. It has been shown that histopathological changes and placental malaria enhance the risk of preeclampsia in pregnant women, especially in primigravidas [ 29 ]. Histopathological changes during placental malaria include presence of hemozoin, perivillous fibrin deposition [ 30 , 31 ], syncytial knot formation [ 32 ], and decrease in villous surface area (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the placenta showed a signi cant number of syncytial knots, brinoid necrosis, calci cation and hyalinization. Meanwhile, Obiri et al (26) in Ghana revealed syncytial knots as the main contributor to placental pathology in women diagnosed with preeclampsia; this was about ten-fold more frequent in preeclampsia than non-preeclampsia placentas. For our case however, endarteritis 93(57.4%) was the most common pathological lesion noted.…”
Section: Discussionmentioning
confidence: 99%